A scientometric review of tourism carrying capacity research: Cooperation, hotspots, and prospect. (20th November 2021) - Li, Jianpu; Weng, Gangmin; Pan, Yue; Li, Conghui; Wang, Ning
Abstract: With the emergence of a series of problems in the tourism sustainable development, such as environmental pollution, landscape destruction, ecological imbalance, and decreased satisfaction of tourists and residents, it is very urgent to research the tourism carrying capacity. Numerous studies have investigated the tourism carrying capacity but none of them provides a comprehensive analysis of the whole field. The purpose of this study was to identify the hot topics, knowledge gaps and future research directions of the tourism carrying capacity research. Based on the bibliometric records of Web of Science core collection database in 2001–2020, the CiteSpace software and the analysis methods of co-authorship analysis, co-citation analysis and co-occurrence analysis were combined to present a holistic review of the tourism carrying capacity research. The results showed that China, Spain and the United States were the major countries in the research of tourism carrying capacity. Five hot research topics were identified: 1) concept and connotation of tourism carrying capacity, 2) index system and performance model of tourism carrying capacity, 3) sustainable management and practical application, 4) social tourism carrying capacity, and 5) sustainable tourism and ecotourism carrying capacity. In addition, four knowledge gaps were identified, and future research directions for bridging these knowledge gaps were also proposed. This study benefits academics, industry practitioners and governments by providing a comprehension of status quo, hot research topics, knowledge gaps and future research directions in the domain of tourism carrying capacity. Highlights: A scientometric review of tourism carrying capacity was conducted. 298 research outcomes of WoS core collection published in 2001–2020 were analyzed. Both quantitative scientometric analysis and qualitative discussion were applied. Hot research topics, knowledge gaps and future research directions were identified.